Virulence Factors in pathogens :mechanisms of infection & disease progression - Alisha Arzoo (International Journal of Pathogens, 2025)
Pathogens, like bacteria, viruses, fungi, and parasites, have evolved specialized tools – known as virulence factors – that help them infect hosts, escape the immune system, and cause disease. These factors play a key role in determining how severe an infection becomes, how quickly it spreads, and how the body responds. Some pathogens use adhesins to stick to host cells, while others produce toxins that damage tissues or disrupt normal immune functions. Additionally, strategies, like capsule formation and antigenic variation, help microbes stay hidden from the immune system, allowing them to persist and multiply. Understanding how virulence factors work is essential for developing better ways to fight infections. Vaccines can be designed to target specific virulence mechanisms, while new antimicrobial drugs aim to block these harmful processes without harming beneficial microbes. Cutting-edge genetic engineering tools, like CRISPR, are also showing promise in disabling virulence-related genes, offering new hope in the fight against infectious diseases. With antibiotic resistance on the rise, shifting our focus from simply killing pathogens to neutralizing their harmful tactics could lead to more effective and sustainable treatments. By continuing to explore these mechanisms, scientists can develop smarter ways to prevent and treat infections, ultimately protecting public health on a global scale.
Keywords: Pathogenesis; Virulence factors; antimicrobial resistance; immune evasion; infectious diseases